Endovascular treatment in comatose patients with anterior circulation ischemic stroke - Sluis, Wouter M.; Uniken Venema, Simone M.; van der Hoorn, Anouk; Bot, Joseph C. J.; van Zwam, Wim H.; Hofmeijer, Jeannette; van der Worp, H. Bart (Frontiers in Neurology, 2025)
BackgroundComa in the first hours after anterior circulation ischemic stroke is rare. We aimed to assess the causes of coma and outcomes after endovascular thrombectomy (EVT) in this relatively unexplored subgroup of patients.Materials and methodsWe used data from the MR CLEAN Registry, a prospective, multicenter, observational cohort study of patients treated with EVT in the Netherlands between March 2014, and December 2018. We included patients with anterior circulation ischemic stroke treated within 6.5 h of symptom onset and assessed frequency and causes of coma, defined as a score of 8 or lower on the Glasgow Coma Scale. Patients with a posterior circulation stroke were excluded. The primary outcome was the score on the modified Rankin Scale at 90 days. We compared outcomes of comatose and non-comatose patients with logistic regression.ResultsFifty-two (1%) of 4,869 patients were comatose. The main causes of coma were bilateral ischemia, a post-ictal state after an epileptic seizure, and respiratory insufficiency. Comatose patients were less likely to receive intravenous thrombolysis (54% vs. 73%; p = 0.004) and onset-to-groin times were longer (226 vs. 199 min; p = 0.012). Patients with coma had poorer functional outcomes (adjusted common odds ratio (OR), 2.73; 95%CI: 1.45–5.13) and more frequently died within 90 days (adjusted OR, 2.95; 95%CI: 1.47–5.90).ConclusionBilateral ischemia, a post-ictal state after an epileptic seizure and respiratory insufficiency are common causes of coma in patients with anterior circulation ischemic stroke treated with EVT. These patients have a high risk of death or dependency at 90 days.